Studi Kasus Kombinasi Centuki (Cendol Daun Katuk Dan Kacang Hijau) Untuk Meningkatkan Produksi Asi Pada Ibu Menyusui Di Puskesmas Banjarnegara 2 - Anita, Debbi Tri; Dewi, Feti Kumala; Hikmanti, Arlyana (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat 2025, 2025)
Breast milk production after childbirth is not always optimal, as it is influenced by physiological and psychological factors. Non-pharmacological interventions using natural ingredients can support successful lactation. CENTUKI contains aliphatic compounds that are effective in increasing breast milk production and vitamin B1, which plays a role in converting carbohydrates into energy, strengthening the nervous system, and supporting breast milk production. This study aimed to identify maternal characteristics and evaluate the effectiveness of the CENTUKI combination (katuk leaf cendol and mung beans) in increasing breast milk volume at Banjarnegara 2 Health Center. This research employed a case study design involving 4 breastfeeding mothers with infants aged 0–6 months. The intervention consisted of administering 500 ml of CENTUKI daily for 5 consecutive days. Data were collected through interviews, observations, and measurements of breast milk volume using a breast pump before and after the intervention. The results showed that the average breast milk volume before intervention was 37.5 ml, which increased to 70 ml after 5 days, with an average increase of 32.5 ml. Respondents’ characteristics were mostly aged 20–35 years (75%), primiparous (75%), housewives (100%), and had a high school education (50%). The CENTUKI combination was proven effective in increasing breast milk production and may serve as a complementary intervention to support the success of exclusive breastfeeding